A novel protocol for dispatcher assisted CPR improves CPR quality and motivation among rescuers—A randomized controlled simulation study. (January 2017) - Rasmussen, Stinne Eika; Nebsbjerg, Mette Amalie; Krogh, Lise Qvirin; Bjørnshave, Katrine; Krogh, Kristian; Povlsen, Jonas Agerlund; Riddervold, Ingunn Skogstad; Grøfte, Thorbjørn; Kirkegaard, Hans; Løfgren, Bo
Abstract: Background: Emergency dispatchers use protocols to instruct bystanders in cardiopulmonary resuscitation (CPR). Studies changing one element in the dispatcher's protocol report improved CPR quality. Whether several changes interact is unknown and the effect of combining multiple changes previously reported to improve CPR quality into one protocol remains to be investigated. We hypothesize that a novel dispatch protocol, combining multiple beneficial elements improves CPR quality compared with a standard protocol. Methods: A novel dispatch protocol was designed including wording on chest compressions, using a metronome, regular encouragements and a 10-s rest each minute. In a simulated cardiac arrest scenario, laypersons were randomized to perform single-rescuer CPR guided with the novel or the standard protocol. Primary outcome: a composite endpoint of time to first compression, hand position, compression depth and rate and hands-off time (maximum score: 22 points). Afterwards participants answered a questionnaire evaluating the dispatcher assistance. Results: The novel protocol (n = 61) improved CPR quality score compared with the standard protocol (n = 64) (mean (SD): 18.6 (1.4)) points vs. 17.5 (1.7) points, p < 0.001. The novel protocol resulted in deeper chest compressions (mean (SD): 58 (12) mm vs. 52 (13) mm, p = 0.02) and improved rate of correct hand position (61% vs. 36%, p = 0.01) compared with the standard protocol. In both protocols hands-off time was short. The novel protocol improved motivation among rescuers compared with the standard protocol (p = 0.002). Conclusions: Participants guided with a standard dispatch protocol performed high quality CPR. A novel bundle of care protocol improved CPR quality score and motivation among rescuers.